Compressive ratcheting and creep of non-asbestos fibre composite considering temperature effect. (November 2018) - Zheng, Xiaotao; Dai, Wenchao; Ma, Linwei; Wang, Wei; Lin, Wei; Yu, Jiuyang
Compressive ratcheting response and creep of non-asbestos fibre composite are tested based on a designed compression–compression clamp for plate-shape specimens. The influences of temperature, stress amplitude and stress rate are discussed in detail. A two-stage constitutive model is developed to describe the compression-resilience relationship of non-asbestos fibre composite. Results present that a crescent-shaped stress–strain relationship of non-asbestos fibre composite is observed under repeated compression, and the proposed two-stage constitutive model can predict the compression-resilience curve for the first cycle very well under various temperatures and stress rates. Additionally, the ratcheting strain of non-asbestos fibre composite obviously enhances with increasing the temperature. However, it has a little change when the stress rate and stress amplitude are varied based on the experimental data. The ratcheting strain rate per cycle reduces promptly during about the first 75 cycles, and it is always less than 1 × 10 −4 per cycle during the subsequent cycles and tends to shakedown. Moreover, the ratcheting strain with small stress amplitude is very close to the creep deformation at the same testing time and peak stress under different temperatures. This indicates that the ratcheting strain of non-asbestos fibre composite under fatigue loads with small stress amplitude can be evaluated equivalently by the corresponding creep deformation with high precision.